Pengembangan Pendidikan Islam Perspektif Jalur Pendidikan Formal di Aimas Kabupaten Sorong - Muhammad Rusdi Rasyid (IAIN Sorong, 2019)
The purpose of this study is; 1) to find and describe community motivation in developing formal Islamic education, 2) describe and analyze the form and type of development of formal Islamic education in Aimas, Sorong Regency. The method of this research is qualitative research with the approach used is the phenomenology approach and the scientific approach in the form of sociological and historical. The data sources of this study are community leaders, coaches, mentors, educators, students, and the community. Furthermore, the data collection methods used were observation, interviews, documentation, and triangulation. The next step is data processing techniques and data analysis carried out through data reduction, data presentation, and data verification. The results of this study indicate that there are two important factors that motivate the development of formal Islamic education in the Aimas transmigrant community in Sorong Regency, namely: 1) low religious understanding, 2) economy. There are three forms of developing formal Islamic education. First, Early Childhood Education (PAUD) in the form of Raudhatul Athfal (RA). Second, Basic Education takes the form of Madrasah Ibtidaiyah (MI) and Madrasah Tsanawiyah (MTs). Third, Secondary Education in the form of Madrasah Aliyah (MA).